Inappropriate Strategies That Senior High School Students Use When Solving Routine Problems in Basic Algebra (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of the study was to identify the inappropriate strategies that senor high school students used when solving routine problems in basic algebra. The study was conducted with second year students of Eguafo Senior High School, Edinaman Senior High School and Komenda Secondary Technical School; all situated in the Central Region of Ghana. The data used in the analysis were collected form 120 students of the various programmes in the Senior High School. The simple random sampling method was used in the selection of the sample and the descriptive sample survey was the research design used. Essay type achievement tests and interview were used in the data collection. The test involved 20 independent test items under 10 routine problems in basic algebra. The test items were carefully selected from various Senior High School Mathematics text books and WAEC past questions under the supervision of the supervisor. Students were assembled in their classrooms for the administration of the tests. The tests were administered during official school hours. A total of thirty students, ten from each school were interviewed individually on their solutions to the test items. The failure strategies identified were observed to have comprised one or some combinations of a number of errors classified into six types as follows: a. Sign Errors, Misconception, Slip-shod Errors, Misapplication of RulesComputational Errors and Miscellaneous Errors. It was recommended that textbook authors in their text books should caution students on the possible common mistakes students make with each topic.